Impact of humate substances and Bacillus subtilis PB6 on thyroid activity and histomorphometry, iron profile and blood haematology of quail. Issue 1 (25th March 2021) - Elnesr, Shaaban S.; Abdel‐Razik, Abdel‐Razik H.; Elwan, Hamada A. M.
Abstract: The purpose of this study was to assess the effects of dietary humate substances (HS) and CloSTAT ( Bacillus subtilis PB6) on the thyroid activity and histology, iron profile, blood haematology and performance of growing Japanese quail. A total of 216 unsexed 7‐day‐old quail chicks were randomly assigned to six groups. The first group was fed a basal diet (BD) without any additives (control); the 2nd group received BD plus 0.05% CloSTAT, the 3rd and 4th groups were given BD plus 0.4% and 0.8% HS, respectively; and the 5th and 6th groups were administered BD plus CloSTAT + 0.4% HS and BD plus CloSTAT + 0.8% HS, respectively. The results showed that the growth performance was improved with the addition of CloSTAT alone or in combination with 0.4% HS compared with the control. Haematological parameters, iron level and transferrin saturation % were significantly ( p  < 0.001) increased by feeding HS compared with the control group. Serum thyroxin and triiodothyronine levels were significantly ( p  = 0.001) increased by adding CloSTAT relative to the control. Supplementation of 0.8% HS caused deterioration in histomorphometry parameters of the thyroid gland, but these parameters were improved in response to CloSTAT compared with the control. In conclusion, dietary B. subtilis PB6 as CloSTAT or CloSTAT + 0.4% HS supplementation may be efficacious in enhancing the growth performance and boosting the thyroid activity of growing Japanese quail. Moreover, the addition of 0.4% or 0.8% HS to quail diets boosted their iron profile and haematological parameters.